2021
DOI: 10.4103/ijri.ijri_618_20
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and radiology: Combating the COVID-19 conundrum

Abstract: The COVID-19 pandemic has necessitated rapid testing and diagnosis to manage its spread. While reverse transcriptase polymerase chain reaction (RT-PCR) is being used as the gold standard method to diagnose COVID-19, many scientists and doctors have pointed out some challenges related to the variability, accuracy, and affordability of this technique. At the same time, radiological methods, which were being used to diagnose COVID-19 in the early phase of the pandemic in China, were sidelined by many primarily du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…5 Regarding chest radiology, both radiographs and CT are interesting in the market because chest radiographs are the most common imaging in the hospitals, especially in the coronavirus disease-2019 (COVID-19) infection era. [21][22][23] Additionally, the amount of lung involvement in patients with COVID-19 for treatment planning and prognosis prediction is important for AI to have higher and faster accuracy in calculation. 21 Much AI research has launched recently; however, a few researchers have tested AI systems in real-world clinical settings, 16,24 and research about AI's true benefits to patients has not been exactly explored.…”
Section: Current Situationsmentioning
confidence: 99%
“…5 Regarding chest radiology, both radiographs and CT are interesting in the market because chest radiographs are the most common imaging in the hospitals, especially in the coronavirus disease-2019 (COVID-19) infection era. [21][22][23] Additionally, the amount of lung involvement in patients with COVID-19 for treatment planning and prognosis prediction is important for AI to have higher and faster accuracy in calculation. 21 Much AI research has launched recently; however, a few researchers have tested AI systems in real-world clinical settings, 16,24 and research about AI's true benefits to patients has not been exactly explored.…”
Section: Current Situationsmentioning
confidence: 99%
“…It was found that early stages of COVID-19 pneumonia in the lungs of COVID affected patients showed differences in imaging from those suffering from other types of pneumonia/viral disease. 5,6 The study concluded that HRCT of the chest was rapidly replacing pathological tests in the early diagnosis of COVID-19 but though AI based radiology models offer many advantages, they warranted larger, well-annotated training datasets for diagnostic utility yet. 5,6 Born et al conducting a meta-analysis of 463 manuscripts established that AI had greater diagnostic accuracy for CT scans than X-ray and concluded that as many as 72% research papers focused predominantly on the use of AI for chest X-ray and for diagnosis purposes more than for severity and prognosis.…”
Section: Aimentioning
confidence: 99%
“…5,6 The study concluded that HRCT of the chest was rapidly replacing pathological tests in the early diagnosis of COVID-19 but though AI based radiology models offer many advantages, they warranted larger, well-annotated training datasets for diagnostic utility yet. 5,6 Born et al conducting a meta-analysis of 463 manuscripts established that AI had greater diagnostic accuracy for CT scans than X-ray and concluded that as many as 72% research papers focused predominantly on the use of AI for chest X-ray and for diagnosis purposes more than for severity and prognosis. 7 Google's DeepMind released AI structure predictions for proteins with high biological significance for the SARS-CoV-2.…”
Section: Aimentioning
confidence: 99%
“…Numerous articles have evaluated the performance of AI systems especially in India where the cohort of patients has been very high, all concluding the experienced radiologists performed better than the AI system in the detection of COVID-19 pneumonia. [19][20][21] Where AI is making a significant impact is on the quantification of extent of lung involvement. In a pandemic, the main concern is as large volumes of patients present at the same time, medical facilities will get overwhelmed triggering panic and societal problems.…”
mentioning
confidence: 99%
“…Numerous articles have evaluated the performance of AI systems especially in India where the cohort of patients has been very high, all concluding the experienced radiologists performed better than the AI system in the detection of COVID-19 pneumonia. 19 20 21 …”
mentioning
confidence: 99%